Harmony, modesty, dialogue : a Moravian contribution towards the development of Christian theologies of religious pluralism - Thompson, Livingstone Anthony (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2003)
Despite the multiplicity of religions, religious aspirations and religious goals, Christians have generally maintained that in Jesus Christ God has been revealed in an unsurpassable way. In modem times, however, Christians themselves have been questioning whether this exclusive position is still plausible given the loss of Christian claims to superior truth. Changes in Christian self-understanding in a plural context have led to the development of theologies of pluralism. The aim of this study is to develop such a discourse from the point of view of the Moravian Church.
Keywords: Theology, Ph.D.; Ph.D. Trinity College Dublin